Sustained photosynthetic performance of Coffea spp. under long-term enhanced [CO2]. - José C Ramalho (Public Library of Science (PLoS), 2013)
Coffee is one of the world's most traded agricultural products. Modeling studies have predicted that climate change will have a strong impact on the suitability of current cultivation areas, but these studies have not anticipated possible mitigating effects of the elevated atmospheric [CO2] because no information exists for the coffee plant. Potted plants from two genotypes of Coffea arabica and one of C. canephora were grown under controlled conditions of irradiance (800 μmol m(-2) s(-1)), RH (75%) and 380 or 700 μL CO2 L(-1) for 1 year, without water, nutrient or root development restrictions. In all genotypes, the high [CO2] treatment promoted opposite trends for stomatal density and size, which decreased and increased, respectively. Regardless of the genotype or the growth [CO2], the net rate of CO2 assimilation increased (34-49%) when measured at 700 than at 380 μL CO2 L(-1). This result, together with the almost unchanged stomatal conductance, led to an instantaneous water use efficiency increase. The results also showed a reinforcement of photosynthetic (and respiratory) components, namely thylakoid electron transport and the activities of RuBisCo, ribulose 5-phosphate kinase, malate dehydrogenase and pyruvate kinase, what may have contributed to the enhancements in the maximum rates of electron transport, carboxylation and photosynthetic capacity under elevated [CO2], although these responses were genotype dependent. The photosystem II efficiency, energy driven to photochemical events, non-structural carbohydrates, photosynthetic pigment and membrane permeability did not respond to [CO2] supply. Some alterations in total fatty acid content and the unsaturation level of the chloroplast membranes were noted but, apparently, did not affect photosynthetic functioning. Despite some differences among the genotypes, no clear species-dependent responses to elevated [CO2] were observed. Overall, as no apparent sign of photosynthetic down-regulation was found, our data suggest that Coffea spp. plants may successfully cope with high [CO2] under the present experimental conditions.